Excitation Induced Tunable Emission in Ce3+/Eu3+ Codoped BiPO4 Nanophosphors - Sarabjot Singh; G. Lakshminarayana; Manoj Sharma; Thang Duy Dao; K. Chen; Yoshiki Wada; T. Takeda; T. Nagao (Journal of Spectroscopy)
Ce3+, Eu3+ ions singly doped, and Ce3+/Eu3+ codoped bismuth phosphate (BiPO4) nanophosphors were synthesized by a simple precipitation method and their structural, morphological, and photoluminescence properties were investigated. The structural and morphological analysis confirms the pure hexagonal crystal structure of the synthesized nanophosphors. From the Fourier transform infrared (FTIR) spectra various absorption bands respective to functional groups such as PO4 and phonon vibrations including the bending modes of the PO4 units are identified. The Ce3+ doped nanophosphors show spectrally broad luminescence in the blue (centred at 459 nm) wavelength region under the direct optical excitation of Ce3+ at 417 nm. For Eu3+ doped nanophosphors, five emission bands have been observed with 394 nm excitation wavelength. Among them, 595 nm has shown bright yellowish-orange emission. These results demonstrate that by appropriately tuning the excitation wavelength of these codoped nanophosphors the emission color in the visible region (blue and orange) can be flexibly controlled in a single sample without varying its chemical composition and size. The mechanism for this excitation energy dependent tunable emission is explained on the basis of nonenergy transfer (ET) occurring among Ce3+/Eu3+ dopant ions.